CANDI GUNUNG GANGSIR AND THE CHARACTER OF THE EARLY EAST JAVANESE ARCHITECTURE - Peter R. Hoffmanns (Berkala Arkeologi, 1987)
In this contribution I would like to draw some attention to a period which is widely considered to be a black hole or a white spot, in any case "a blank in Indonesian archaeology" (Soekmono 1969:3). It needs no explanation that I am alluding to the period of the tenth until the thirteenth century A.D.